2011
DOI: 10.1111/j.1741-3729.2010.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

“I luv u :)!”: A Descriptive Study of the Media Use of Individuals in Romantic Relationships

Abstract: In this study, we address the communication technologies individuals within romantic relationships are using to communicate with one another, the frequency of use, and the association between the use of these technologies and couple's positive and negative communication. Participants consisted of individuals involved in a serious, committed, heterosexual relationship. The Relationship Evaluation Questionnaire instrument was used to assess a variety of relationship variables. The majority of individuals within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
155
0
20

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(183 citation statements)
references
References 25 publications
8
155
0
20
Order By: Relevance
“…A su vez, el no estar presente puede llevar a la pareja a experimentar bajos niveles de sa sfacción en la relación y bajos niveles de romancismo (McDaniel & Coyne, 2016;Roberts & David 2016). Existen algunos estudios que tratan el tema de la interferencia de aparatos electrónicos en las relaciones de pareja (Coyne et al, 2011;McDaniel & Coyne, 2016). La mayoría de estos estudios encontraron que el uso excesivo de la tecnología, ya sean smartphones u otros aparatos electrónicos, genera conflictos y problemas en las relaciones de pareja, afectando, consecuentemente, el bienestar y la sa sfacción de la misma.…”
Section: Phubbing Y Relaciones Román Casunclassified
See 2 more Smart Citations
“…A su vez, el no estar presente puede llevar a la pareja a experimentar bajos niveles de sa sfacción en la relación y bajos niveles de romancismo (McDaniel & Coyne, 2016;Roberts & David 2016). Existen algunos estudios que tratan el tema de la interferencia de aparatos electrónicos en las relaciones de pareja (Coyne et al, 2011;McDaniel & Coyne, 2016). La mayoría de estos estudios encontraron que el uso excesivo de la tecnología, ya sean smartphones u otros aparatos electrónicos, genera conflictos y problemas en las relaciones de pareja, afectando, consecuentemente, el bienestar y la sa sfacción de la misma.…”
Section: Phubbing Y Relaciones Román Casunclassified
“…Asimismo, otros autores asocian la presencia y/o u lización de teléfonos inteligentes con baja sa sfacción y poca cercanía/conexión con la pareja (Przybylski & Weinstein, 2013;Roberts & David, 2016). Lo preocupante de este asunto es que todos los estudios revisados indican que el phubbing y el uso de aparatos electrónicos son una prác ca común y conflic va en las relaciones de pareja (Coyne et al, 2011;Lenhart & Duggan, 2014). Basado en lo expuesto en este apartado, esperamos que nuestro estudio correlacione estadís camente el phubbing percibido por la pareja con la sa sfacción en la relación.…”
Section: Phubbing Y Relaciones Román Casunclassified
See 1 more Smart Citation
“…This is a plausible hypothesis considering that narcissism is associated with more frequent social media use (Carpenter, 2012;Panek, Nardis, & Konrath, 2013), and that studies have found that mobile phones can reduce people's empathy, feelings of closeness, feelings of trust, and prosocial behaviors (Abraham, Pocheptsova, & Ferraro, 2012;Przybylski & Weinstein, 2013). Yet even though mobile phones may distract people from face-to-face interactions under some circumstances, they also literally connect us to others, making us feel closer to loved ones when there is physical distance ("Always connected: How Smartphones and Social Keep Us Engaged," 2013; Coyne, Stockdale, Busby, Iverson, & Grant, 2011;Faulkner & Culwin, 2005;Padilla-Walker, Coyne, & Fraser, 2012;Pettigrew, 2009). Technologies are simply tools, and with the introduction of new technologies, there are often struggles to make sense of them and optimize their potential (Postman, 1992).…”
Section: The Malleability Of Empathymentioning
confidence: 99%
“…The role technology plays in teen sexual relationships should be part of sex education and also recognised within anti-bullying practice -both central areas of school nurse practice (Hayter et al 2012) Most young people own a device capable of sending and receiving texts and the use of such devices is one of the main vehicles of peer to peer communication. This is especially true of intimate relationships where texting is used to initiate, arrange and conduct relationships -often regarded by the users as a safe, intimate and possibly secret method of communication (Coyne et al 2011). Hand held devices help to facilitate this by not requiring time at a computer or even in the home.…”
Section: Introductionmentioning
confidence: 99%